2020
DOI: 10.7554/elife.57183
|View full text |Cite|
|
Sign up to set email alerts
|

A two-lane mechanism for selective biological ammonium transport

Abstract: The transport of charged molecules across biological membranes faces the dual problem of accommodating charges in a highly hydrophobic environment while maintaining selective substrate translocation. This has been the subject of a particular controversy for the exchange of ammonium across cellular membranes, an essential process in all domains of life. Ammonium transport is mediated by the ubiquitous Amt/Mep/Rh transporters that includes the human Rhesus factors. Here, using a combination of electrophysiology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 66 publications
(103 reference statements)
4
53
1
Order By: Relevance
“…Moreover, both strains depleted ammonium to comparable levels of about 1.2 mg l -1 or 67 µmol l -1 , well in line with previously reported values for E. coli K-12 strains in nitrogen limited chemostats (Hua et al, 2004). The low remaining ammonium concentration indicates that uptake in both strains is mediated actively by AmtB with K m = 0.8 mM (Williamson et al, 2020) and incorporation is accomplished by the GS-GOGAT System with GS K m = 0.1 mM (Alibhai and Villafranca, 1994). This is supported by our transcriptional data which revealed that amtB, gltB and gltD were significantly enriched for both strains over all time-points.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, both strains depleted ammonium to comparable levels of about 1.2 mg l -1 or 67 µmol l -1 , well in line with previously reported values for E. coli K-12 strains in nitrogen limited chemostats (Hua et al, 2004). The low remaining ammonium concentration indicates that uptake in both strains is mediated actively by AmtB with K m = 0.8 mM (Williamson et al, 2020) and incorporation is accomplished by the GS-GOGAT System with GS K m = 0.1 mM (Alibhai and Villafranca, 1994). This is supported by our transcriptional data which revealed that amtB, gltB and gltD were significantly enriched for both strains over all time-points.…”
Section: Discussionsupporting
confidence: 90%
“…Ammonium transporters in other species are highly selective for ammonium, with little to no transport of larger amines [34, 35], in accordance with the narrow tuning of Amt/Rh50 + ORNs to ammonia (Figure 2A). Further, ammonium transporters are electrogenic, mediating inward, depolarizing NH 4 + influx [17, 18, 35, 36]. Given that ammonia (NH 3 ) gas is expected to form ammonium ions (NH 4 + ) in the sensillum lymph, these cations could be transported through either Amt or Rh50 and depolarize the ORNs.…”
Section: Resultsmentioning
confidence: 99%
“…The narrowly tuned ammonia response in these ORNs (Figure 2A) is consistent with the strict selectivity of ammonium transporters. 36,37 Amts also distinguish NH 4 + ions from similarly sized K + ions, 17,37,38 an advantage considering the presence of >100 mM K + in the sensillum lymph bathing ORN dendrites. We propose that a simple electrogenic influx of ammonium ions leads to ORN depolarization, but we cannot rule out an ammonium-initiated signaling cascade analogous to the mechanism for vertebrate sour sensing, in which H + influx closes acid-sensitive K + channels.…”
Section: Discussionmentioning
confidence: 99%
“…Further, ammonium transporters are electrogenic, mediating inward NH 4 + currents. 16,17,37,38 Given that NH 3 gas is expected to form ammonium ions (NH 4 + ) in the sensillum lymph, these cations could be transported through either Amt or Rh50 and depolarize the ORNs. In this manner, the transporters could act as ammonia-selective receptors.…”
Section: Amt As An Ammonia Receptormentioning
confidence: 99%